Digital Development Influencing Mechanism on Green Innovation Performance: A Perspective of Green Innovation Network - Huan Yu Li; Qin Liu; Han Zhang Ye (IEEE Access, 2023)
Digital development offers groundbreaking opportunities for environmental monitoring and protection, as well as for maintaining the overall health of the planet. Through judicious use, global sustainability can be promoted. This study constructs a green innovation network using the green innovation patent data of listed companies of new energy vehicles as empirical evidence. The influence of network structure on green innovation performance is analyzed, and network structure indicators with positive effects are identified. The Exponential Random Graph Model (ERGM) is used to analyze the evolutionary influence on the structure of green innovation network from network configuration as endogenous attributes and digital characteristics as exogenous attributes. We explore the mechanism of improving green innovation performance by digitalization through enhancing the development of green innovation network. The results show that the enhanced structure of innovation network has a significant positive effect on the improvement of green innovation performance. Both “star” and “closed triangle” network configurations can promote the establishment of green innovation cooperation. In terms of digital characteristics, digital technology and digital organization can positively promote the development of green innovation network, while digital environment does not show a significant facilitating effect. Because of the tremendous expansion of digital technology adoption and the necessary infrastructure, enterprises can bridge the technology gap by optimizing digital technology and digital organizations. Enterprises can improve green innovation performance by optimizing digital technology and digital organization to promote the establishment of green innovation cooperation. The government should avoid the ineffective empowerment of digital environment construction on green innovation performance.